Simple and reproducible HPLC-DAD-ESI-MS/MS analysis of alkaloids in Catharanthus roseus roots - Ferreres, F.; Pereira, D.M.; Valentao, P.; Oliveira, J.M.A.; Faria, J.; Gaspar, L.; Sottomayor, M.; Sottomayor, M.
Catharanthus roseus is one of the most important medicinal plants worldwide. The leaves of this species are the only source of the indolomonoterpenic alkaloids vincristin (leurocristine)and vinblastin (vincaleucoblastine), whose anticancer activity represents powerful therapeutics to many diseases, such as Hodgkin lymphoma. Usually, the remaining plant parts go to waste. Here we describe a phytochemical study on this species roots. Alkaloids in aqueous extracts, the usual form of consumption of this matrix, were studied using HPLC-DAD-ESI-MS/MS, which allowed the identification of 19-S-vindolinine, vindolinine, ajmalicine and an ajmalicine isomer, tabersonine, catharanthine, serpentine and a serpentine isomer. Quantification of the identified compounds revealed that serpentine and its isomer were predominant (64.7
Keywords: CATHARANTHUS ROSEUS; ROOTS; HPLC-DAD-ESI-MS/MS; ALKALOIDS